The Effect of Fructose Level and Prostate Specific Antigen (PSA) on Sperms Motility in InFertiled Men - Aiesha saadoun jassim; Hussain Khleefa Kazem; Nezar Ahemad Naje (Tikrit Journal of Pure Science)
The aim of  this the study was to evaluate the clinical situations by measuring the concentration of fructose and prostate specific antigen(PSA), as well as studying  the causes and risk factors of infertiled men .